2019
DOI: 10.1002/yea.3375
|View full text |Cite
|
Sign up to set email alerts
|

The reported point centromeres of Scheffersomyces stipitis are retrotransposon long terminal repeats

Abstract: Point centromeres, found in some ascomycete yeasts such Saccharomyces cerevisiae, are very different in structure from the centromeres of other eukaryotes. They are tiny and nonrepetitive and contain only two short conserved sequence motifs. Until recently, point centromeres were thought to have a single evolutionary origin, in the budding yeast family Saccharomycetaceae. Most yeasts outside this family have centromeres that are many kilobases in size. Some have centromeres consisting of a large inverted repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Strikingly, we observed that a single degenerated LTR retrotransposon, VdLTRE9 , is strongly associated with centromeres in some Verticillium species, while it is absent from LS regions in V. dahliae . The association of specific retrotransposons with centromeres has also been observed in the yeasts Ogataea polymorpha ( 69 ), Debaryomyces hansenii ( 68 ), and Scheffersomyces stipitis ( 70 ), where a retrotransposon related to Ty5 is enriched at centromeres. Similarly, centromeres in Cryptococcus contain six retrotransposons ( Tcn1 to - 6 ) that occur nearly exclusively at centromeres ( 16 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Strikingly, we observed that a single degenerated LTR retrotransposon, VdLTRE9 , is strongly associated with centromeres in some Verticillium species, while it is absent from LS regions in V. dahliae . The association of specific retrotransposons with centromeres has also been observed in the yeasts Ogataea polymorpha ( 69 ), Debaryomyces hansenii ( 68 ), and Scheffersomyces stipitis ( 70 ), where a retrotransposon related to Ty5 is enriched at centromeres. Similarly, centromeres in Cryptococcus contain six retrotransposons ( Tcn1 to - 6 ) that occur nearly exclusively at centromeres ( 16 ).…”
Section: Discussionmentioning
confidence: 81%
“…Centromeres are often enriched for a variety of different retrotransposons and other repetitive elements ( 15 , 16 , 25 , 29 , 30 , 68 70 ). We similarly observed that centromeres in all Verticillium species are repeat rich.…”
Section: Discussionmentioning
confidence: 99%
“…Following assembly, BUSCO v3 was run to assess gene space (9), identifying the presence of 1683 conserved genes from the Saccharomycetales_odb9 gene database. Assembly size and contiguity statistics were assessed using QUAST v4.5 (10) The final assembly in contigs was further corrected and assembled to chromosome level by identification of centromeric sequences and overlapping regions between the contigs (11).…”
Section: Methodsmentioning
confidence: 99%
“…Although several S. stipitis natural isolates are used for the optimisation of second-generation biofuels production, the genome of only one strain (Y-11545) has been sequenced and assembled to the chromosomal level (60). The Y-11545 strain has a genome organised in 8 chromosomes containing transposon-rich regional centromeres (11, 60, 61).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation